Second Generation IMO Intact Stability Vulnerability Criteria and its Application to ships Navigating in Persian Gulf and Oman Sea - Esmaeel Masoudi (International Journal of Maritime Technology, 2017)
Second generation intact stability criteria for few past years had been under development by International Maritime Organization (IMO). Since the draft proposed amendments shall be amended to International code on Intact Stability (IS code 2008), new regulations shall enter into force for ships of length more than 24 meter. Generally second generation intact stability criteria (SGISC) refers to vulnerability ship stability modes which occurs when the ship navigating in rough seas. As waves passes the ship, dynamic phenomenon will affects ship stability that may lead to capsizing. Unlike IS code 2008, which study ship stability in calm water with a single level criteria, SGISC check the stability in different levels. In this method, if a ship passes only one level of criteria, means it is safe according to respective dynamic phenomena. In this article in order to understand the functionality of the proposed criteria in last draft amendment provided by IMO, numerical tools have been used to assess the effect of three phenomenon, pure loss of stability, parametric rolling, and surf-riding/broaching. Wide range of ships including fishing, passenger, cargo, Fiber glass and container ships, navigating in Persian gulf and Oman sea are considered to assess a comprehensive effects of proposed criteria. The results shows that all ships pass pure loss of stability and parametric rolling criteria but all passenger ships, 2 tugs, 1 fiberglass and 1 fishing vessel failed the surf riding/broaching criteria. It should be concluded that to pass the vulnerability criteria of surf riding, existing ships (specially passenger ships) should decrease their speed and new building vessels should be designed so that their Froude number do not encounter critical Froude number range as defined by the regulations.